2015
DOI: 10.1111/zph.12216
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Affecting Detection of Hepatitis E Virus on Canadian Retail Pork Chops and Pork Livers Assayed Using Real‐Time RTPCR

Abstract: We collected 599 Canadian retail pork chops and 283 pork livers routinely (usually weekly) from April 2011 to March 2012 using the Canadian Integrated Program for Antimicrobial Resistance Surveillance (CIPARS) retail sampling platform. Samples were assayed using validated real-time (q) reverse transcriptase polymerase chain reaction (RT-PCR) and nested classical RT-PCR for the detection of hepatitis E virus (HEV), porcine enteric calicivirus (PEC) and rotavirus (RV). The presence of Escherichia coli, Salmonell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(47 reference statements)
2
5
0
Order By: Relevance
“…In our study, 1034 ham muscles collected at the slaughterhouse were examined for the presence of HEV RNA and were found to be negative (Table 1). These results are consistent with the findings of Leblanc et al (2010), Berto et al (2012) and Wilhelm et al (2015) who were unable to detect HEV RNA in loins, ventral abdominal muscles and pork chops respectively. Three percent of 112 lingual muscles sampled at the slaughterhouse were found to be HEV RNA positive in the study by Di Bartolo et al (2012).…”
Section: Hev Prevalence In Pork Musclessupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, 1034 ham muscles collected at the slaughterhouse were examined for the presence of HEV RNA and were found to be negative (Table 1). These results are consistent with the findings of Leblanc et al (2010), Berto et al (2012) and Wilhelm et al (2015) who were unable to detect HEV RNA in loins, ventral abdominal muscles and pork chops respectively. Three percent of 112 lingual muscles sampled at the slaughterhouse were found to be HEV RNA positive in the study by Di Bartolo et al (2012).…”
Section: Hev Prevalence In Pork Musclessupporting
confidence: 92%
“…Di Bartolo et al (2012) also showed that lingual muscles could be contaminated at the slaughterhouse. In contrast, in the UK in 2012, none of the 40 ventral abdomen muscles sampled at a processing plant by Berto et al (2012) were HEV positive, nor were the 43 pork loins or 599 pork chops sampled in Canada at slaughter and retail (Leblanc et al, 2010;Wilhelm et al, 2015). Overall, data regarding the prevalence of HEV in muscles and the associated viral load are either scarce or lacking.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In sharp contrast, the rate of detection of HEV in pig livers outside Asia, where HEV genotype 3 predominates (27), is much higher. In North America, the prevalence of HEV contamination in retail pig livers typically ranges from 5% to 10% (28,29). In Europe, the prevalence is even higher and can reach up to over 40% in very-high-risk pig liver-derived food products, such as figatellu (12,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Requiring shower‐in and providing boots for visitors were significant predictors (p < 0.05) in single fixed‐effect mixed logistic regression analysis for reduced detection of HEV. Such biosecurity measures and not obtaining feeder pigs from multiple sources were associated with reduced odds of detecting HEV (Wilhelm et al., ).…”
Section: Assessmentmentioning
confidence: 99%